The Effect of Birthball Training to Back Pain in Third Trimester Pregnant Women in Kabila Community Health Center - Puspita Sukmawaty Rasyid; Yusni Igirisa (Humanistic Network for Science and Technology (HNST), 2019)
Back pain is one of the inconveniences which is often experienced by third trimester pregnant women. Around 50-72% of women who suffer lower back pain when they are pregnant, this pain will increase as the gestational age increases. This research aims to identify the effect of birthball training to back pain experienced by third trimester pregnant women at the working area of Kabila Community Health Center in Bone Bolango Districts. This research was included in Quasi experimental which is by one group pretest and posttest design.The data analysis used univariate analysis, bivariate analysis uses statistic test t test in two paired samples. The sampling was done by choosing sample that meets the research criteria until a certain period of time until the total samples were fulfilled. The data analysis used univariate analysis and bivariate analysis. The research result obtains that there was a difference of back pain before and after doing birthball training to third trimester pregnant women at the working area of Kabila Community Health Center in Bone Bolango Districts. The advice for Community Health Center party is to improve service quality and prevent back pain to third trimester pregnant women and also makes birthball training as the effort to decrease pregnant women’s inconveniences so that the procedure of fixed birthball training is needed to be applied regularly and monitored. Keywords: Birthball training, Back pain, Pregnant